Critical factors to inhibit water‐splitting side reaction in carbon‐based electrode materials for zinc metal anodes. Issue 6 (20th July 2022) - Kang, Dong Hyuk; Lee, Eunji; Youn, Beom Sik; Ha, Son; Hyun, Jong Chan; Yoon, Juhee; Jang, Dawon; Kim, Kyoung Sun; Kim, Hyungsub; Lee, Sang Moon; Lee, Sungho; Jin, Hyoung‐Joon; et al.
Abstract: Zinc metal anodes (ZMA) have high theoretical capacities (820 mAh g −1 and 5855 mAh cm −3 ) and redox potential (−0.76 V vs. standard hydrogen electrode), similar to the electrochemical voltage window of the hydrogen evolution reaction (HER) in a mild acidic electrolyte system, facilitating aqueous zinc batteries competitive in next‐generation energy storage devices. However, the HER and byproduct formation effectuated by water‐splitting deteriorate the electrochemical performance of ZMA, limiting their application. In this study, a key factor in promoting the HER in carbon‐based electrode materials (CEMs), which can provide a larger active surface area and guide uniform zinc metal deposition, was investigated using a series of three‐dimensional structured templating carbon electrodes (3D‐TCEs) with different local graphitic orderings, pore structures, and surface properties. The ultramicropores of CEMs are the determining critical factors in initiating HER and clogging active surfaces by Zn(OH)2 byproduct formation, through a systematic comparative study based on the 3D‐TCE series samples. When the 3D‐TCEs had a proper graphitic structure with few ultramicropores, they showed highly stable cycling performances over 2000 cycles with average Coulombic efficiencies of ≥99%. These results suggest that a well‐designed CEM can lead to high‐performance ZMA in aqueous zinc batteries. Abstract : A comparative study on a series of three‐dimensional structured templating carbon electrodes with different local graphitic orderings, pore structures, and surface properties was conducted systematically to understand the key factors inhibiting the water‐splitting side reaction during the zinc metal deposition/dissolution processes.